Diagnostic values of chest pain history, ECG, troponin and clinical gestalt in patients with chest pain and potential acute coronary syndrome assessed in the emergency department - Mokhtari, Arash (Springerplus, 2015)
In the assessment of chest pain patients with suspected acute coronary syndrome (ACS) in the emergency department (ED), physicians rely on global diagnostic impressions (‘gestalt’). The aim of this study was to determine the diagnostic value of the ED physician’s overall assessment of ACS likelihood, and the values of the main diagnostic modalities underlying this assessment, namely the chest pain history, the ECG and the initial troponin result. 1,151 consecutive ED chest pain patients were prospectively included. The ED physician’s interpretation of the chest pain history, the ECG, and the global likelihood of ACS were recorded on special forms. The discharge diagnoses were retrieved from the medical records. A chart review was carried out to determine whether patients with a non-ACS diagnosis at the index visit had ACS or suffered cardiac death within 30 days. The gestalt was better than its components both at ruling in (“Obvious ACS”, LR 29) and at ruling out (“No Suspicion of ACS”, LR 0.01) ACS. In the “Strong suspicion of ACS” group, 60% of the patients did not have ACS. A positive TnT (LR 24.9) and an ischemic ECG (LR 8.3) were strong predictors of ACS and seemed superior to pain history for ruling in ACS. In patients with a normal TnT and non-ischemic ECG, chest pain history typical of AMI was not a significant predictor of AMI (LR 1.9) while pain history typical of unstable angina (UA) was a moderate predictor of UA (LR 4.7). Clinical gestalt was better than its components both at ruling in and at ruling out ACS, but overestimated the likelihood of ACS when cases were assessed as strong suspicion of ACS. Among the components of the gestalt, TnT and ECG were superior to the chest pain history for ruling in ACS, while pain history was superior for ruling out ACS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-015-0992-9) contains supplementary material, which is available to authorized users.